Demographics and post-mortem toxicology findings in deaths among people arrested multiple times for use of illicit drugs and/or impaired driving. (August 2016) - Ahlner, Johan; Holmgren, Anita; Jones, Alan Wayne
Highlights: People arrested multiple times for drug-related offences have shorter life expectancy. Accidental overdosing with drugs was a common manner of death in repeat offenders. In 44% of poisoning deaths four or more drugs were identified in autopsy blood samples. Illicit recreational drugs, such as heroin, cannabis and amphetamine were common findings. The major prescription drugs identified in blood were opioid analgesics and sedative-hypnotics. Abstract: Background: Multiple arrests for use of illicit drugs and/or impaired driving strongly suggests the existence of a personality disorder and/or a substance abuse problem. Methods: This retrospective study (1993–2010) used a national forensic toxicology database (TOXBASE), and we identified 3943 individuals with two or more arrests for use of illicit drugs and/or impaired driving. These individuals had subsequently died from a fatal drug poisoning or some other cause of death, such as trauma. Results: Of the 3943 repeat offenders 1807 (46%) died from a fatal drug overdose and 2136 (54%) died from other causes ( p  < 0.001). The repeat offenders were predominantly male (90% vs 10%) and mean age of drug poisoning deaths was 5 y younger (mean 35 y) than other causes of death (mean 40 y). Significantly more repeat offenders (46%) died from drug overdose compared with all other forensic autopsies (14%) ( p  < 0.001). Four or more drugs were identified in femoral blood in 44% of deaths from poisoning (drug overdose) compared with 18% of deaths by other causes ( p  < 0.001). The manner of death was considered accidental in 54% of deaths among repeat offenders compared with 28% for other suspicious deaths ( p  < 0.001). The psychoactive substances most commonly identified in autopsy blood from repeat offenders were ethanol, morphine (from heroin), diazepam, amphetamines, cannabis, and various opioids. Conclusions: This study shows that people arrested multiple times for use of illicit drugs and/or impaired driving are more likely to die by accidentally overdosing with drugs. Lives might be saved if repeat offenders were sentenced to treatment and rehabilitation for their drug abuse problem instead of conventional penalties for drug-related crimes.